1986
DOI: 10.1093/mutage/1.5.343
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity testing of the pyrethroid insecticide cypermethrin in Drosophila

Abstract: The pyrethroid insecticide cypermethrin was tested for the induction of genetic damage in male germ cells of Drosophila melanogaster. Sex-linked recessive lethals, sex-chromosome loss and non-disjunction were studied following different routes of administration: adult feeding, injection and larval feeding. Our results show that, after adult injection and larval ingestion, cypermethrin induces a small but significant increase in the frequency of sex-linked recessive lethal mutations. However, no significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Cypermethrin crosses placental barrier and produces harmful effects in embryo even at very low concentrations. Exposure to cypermethrin reduces DNA content and may lead to mutation, especially germline mutation leading to teratological deformities [32, 38, 39]. Cypermethrin produces mutagenicity and genotoxicity by interacting with DNA metabolic processes, sister chromatid exchange and free radical generation machinery [40, 41].…”
Section: Dna Damagementioning
confidence: 99%
“…Cypermethrin crosses placental barrier and produces harmful effects in embryo even at very low concentrations. Exposure to cypermethrin reduces DNA content and may lead to mutation, especially germline mutation leading to teratological deformities [32, 38, 39]. Cypermethrin produces mutagenicity and genotoxicity by interacting with DNA metabolic processes, sister chromatid exchange and free radical generation machinery [40, 41].…”
Section: Dna Damagementioning
confidence: 99%
“…Surrallés et al (1990) also described a strong inhibition of cell cycle progression and an increased frequency of micronuclei induced by fenvalerate in cultured human lymphocytes, indicating its clastogenic and/or aneugenic activity. On the other hand, reports suggesting no genotoxic effects of fenvalerate have also been published (Hadnagy et al, 1999;Batiste-Alentorn et al, 1986;Herrera and Laborda, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Cypermethrin has been reported to induce gene mutations in male germ cells of Drosophila (Batiste-Alentorn et al, 1986) and genotoxicity and sperm abnormality in mice (Bhunya and Pati, 1988). Surrallés et al (1995b), studying whole blood and isolated human lymphocyte cultures, reported that cypermethrin has a weak genotoxic activity in vitro.…”
Section: Introductionmentioning
confidence: 99%